2015
DOI: 10.1186/s13046-015-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination of curcumin and bicalutamide enhanced the growth inhibition of androgen-independent prostate cancer cells through SAPK/JNK and MEK/ERK1/2-mediated targeting NF-κB/p65 and MUC1-C

Abstract: BackgroundProstate cancer is one of the most common malignancies in men. The mucin 1 (MUC1) heterodimeric oncoprotein is overexpressed in human prostate cancers with aggressive pathologic and clinical features, resulting in a poor outcome. However, the functional role for MUC1 C-terminal domain (MUC1-C) in androgen-independent prostate cancer occurrence and development has remained unclear.MethodsCell viability was measured by MTT assays. Western blot analysis was performed to measure the phosphorylation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…Studies have highlighted the increased expression of MUC1 and its role in tumorigenesis in various cancer types including prostate cancer274546. Our results illustrated both transcriptional and translational regulations of MUC1 by solamargine, and demonstrated a critical role of MUC1 expression in mediating the effect of solamargine on inhibition of growth of CRPC cell.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Studies have highlighted the increased expression of MUC1 and its role in tumorigenesis in various cancer types including prostate cancer274546. Our results illustrated both transcriptional and translational regulations of MUC1 by solamargine, and demonstrated a critical role of MUC1 expression in mediating the effect of solamargine on inhibition of growth of CRPC cell.…”
Section: Discussionsupporting
confidence: 63%
“…MUC1 has been shown to bind to transcriptional factor, such as nuclear factor NF-kappaB (NF-κB)/p65, and promote downstream target gene expression23. We recently showed that curcumin inhibited growth of CRPC cells through multiple kinase-mediated inhibition of MUC1 protein27. However, the expression and functional significance of MUC1 gene in occurrence and progression of CRPC still remains poorly understood.…”
mentioning
confidence: 99%
“…As an oncogenic factor, overexpressed MUC1 was observed in several epithelial cancers, including prostate cancer [32,49]. The regulation and interaction between p65 and MUC1 were also demonstrated in other studies [34,50,51]. By binding to the promoter regions, the MUC1/NF-κB complex could promote certain gene expression in different cancer cells [34,52].…”
Section: Discussionmentioning
confidence: 55%
“…PRDX1 overexpression is also found in human prostate cancer specimens and prostate cancer cell lines [17,100]. Prostate cancer risk and prognosis are adversely associated with a number of inflammatory and angiogenic mediators, including Toll-like receptor 4 (TLR4), NF-jB and VEGF [101][102][103][104]. Elevated PRDX1 increases prostate tumour vasculature, and shows up-regulation of angiogenic proteins such as VEGF in the tumour region.…”
Section: Prdx1 and Prostate Cancermentioning
confidence: 99%